EMISI GAS BUANG KENDARAAN BERMOTOR BERBAHAN BAKAR GAS CAIR (LGV) DAN PERTAMAX PADA KONDISI UJI AWAL DINGIN DAN PANAS - Prawoto, Prawoto (Jurnal Teknologi Lingkungan, 2011)
Liquid Gas Vehicle (LGV) is one of an alternative hydrocarbon fuel, which is the dominant composition are propane and butane, and now is already available in the market. With low sulfur content and high octane number, theoritically vehicle emissions using LGV are better than gasoline. But it is need a good mixture ratio of air to LGV (AFR) in the gas mixer before enter to the engine. This paper describes a study that compared emission test results from gasoline engine using LGV with standard mixer and Pertamax market fuel. The study was based on the vehicle chassis dynamometer test results according to the UN-ECE R83-04 test cycle standard on both cold and hot starts. The test results have shown that on urban cycle CO and HC emissions of Pertamax fuel was better than LGV on both cold and hot starts. Whereis on extra urban cycle CO emission of LGV fuel was better than Pertamax. NOx emission of LGV fuel was very low and practically undetected for all test condition. Utilisation of LGV fuel reduce CO2 emission in order of 15% for urban drive cycle for both cold and hot start, and in order of 9,2% for cold start and 10.5% for hot start for mixed cycle.